2020
DOI: 10.1101/2020.12.04.20244129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-harm and the COVID-19 pandemic: a study of factors contributing to self-harm during lockdown restrictions

Abstract: IntroductionThe COVID-19 pandemic and resulting public health measures may have major impacts on mental health, including on self-harm. We have investigated what factors related to the pandemic influenced hospital presentations following self-harm during lockdown in England.MethodMental health clinicians assessing individuals aged 18 years and over presenting to hospitals in Oxford and Derby following self-harm during the period March 23rd to 17th May 2020 recorded whether the self-harm was related to the impa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
1
25
1
2
Order By: Relevance
“…In one UK study, 'stay-at-home' related issues contributed to around half of cases, more so in males than females. The most frequent COVID-related factors were mental health issues, including new and worsening disorders, cessation, reduction or transformation of services (including absence of face-to-face support), isolation and loneliness, reduced contact with key individuals, disruption to normal routine, and entrapment (Hawton et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…In one UK study, 'stay-at-home' related issues contributed to around half of cases, more so in males than females. The most frequent COVID-related factors were mental health issues, including new and worsening disorders, cessation, reduction or transformation of services (including absence of face-to-face support), isolation and loneliness, reduced contact with key individuals, disruption to normal routine, and entrapment (Hawton et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that young adults with mental health problems who still live with parents have a higher likelihood of receiving adequate mental health care compared with those who have moved out of the parental home (Copeland et al., 2015 ). These differences may be exacerbated during lockdowns when psychological services may be more difficult to access (Hawton et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For young adults living alone, lockdowns may increase social isolation and loneliness, which are risk factors for self‐injury (Hawton et al., 2021 ; Shaw et al., 2021 ). By contrast, living with (supportive) others (e.g., parents, peers, or intimate partners) during a pandemic may be protective because these relationships are typically important sources of social support, which counteracts psychological problems (Finan, Ohannessian, & Gordon, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also appears to be failing, to varying degrees, to follow media guidelines in relation to key, evidence-informed recommendations, including, for example, the omission of details of suicide methods and sensational language, and inclusion of potential sources of help and support information for readers. Whilst overall standards of reporting have improved over recent years (Fraser et al, 2017), and many reports examined in this study included messages deemed to be positive, the scale and reach of the current crisis underscores the urgent need for further improvements and more cautious reporting (Hawton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that important aspects of the pandemic and its potential influence on suicidal behaviour have been appropriately and comprehensively recorded, the coding scheme was adapted from the 'Classification of COVID-19 related factors involved in self-harm' used in an investigation of hospital attendances for self-harm in the Multicentre Study of Self-harm in England (Hawton et al, 2020). For other sections of the scheme, codes (where not binary yes/no categories) were derived inductively for content (Elo and Kyngäs, 2008) and refined through an iterative process of development and piloting (by three independent raters (MH, EHS and YL)), at different stages of the data collection process.…”
Section: Covid-19 Related News Storiesmentioning
confidence: 99%